Inactivity stochastic precedence order. Issue 8 (18th April 2022) - Misra, Amit Kumar; Gupta, Vaishali; Chanchal, Ruby
Abstract: The aim of this article is to extend the inactivity probability order, defined by Abouelmagd et al. ( Communications in Statistics-Theory and Methods 47, 3293–3304, 2018), to the case of non independent random variables. It is done by defining a new stochastic order based on the inactivity times of two non negative dependent random variables and the stochastic precedence order. Some characterizations and preservation properties of the new stochastic order have been developed. Also, some of its reliability properties and its relation with the other existing well known stochastic orders have been studied. We also discuss some applications of the derived results.